Environmental effects on reproductive performance of Nellore cows widely raised in the Cerrado/Pantanal ecotone (Acta Scientiarum. Animal Sciences, 2015)
We analyzed the pregnancy rate (PR) and birth rate (BR) of Nellore cows raised extensively in the Cerrado/Pantanal during 4 mating seasons (2009–2012), assessing the relationship with the temperature and humidity index (THI) and the effect of the year and breeding season. We used information from 2,116 cows, which were categorized as either multiparous (n = 1430), primiparous (n = 338), or nulliparous (n = 348). In the months of the breeding season (December–February), temperature and relative humidity data were collected to calculate the temperature and humidity index (THI). An ANOVA was performed with a model that included sources of variation from the fixed effects of category of cow and year on PR and BR; and a linear regression analysis and correlation between THI and PR and BR. We observed a significant effect (p < 0.05) on PR. We classified the average across breeding seasons as a moderate THI. The THI of the breeding seasons showed high and significant (p < 0.05) effects only on the nulliparous BR, and low values in other categories. It is concluded that the seasonal THI was not related to the performance of cows, except BR in nulliparous cows.